Enhancing photocurrent efficiencies by resonance energy transfer in CdTe quantum dot multilayers: Towards rainbow solar cells - Ruland Palaia, Andres; Schulz-Drost, Christian; Sgobba, Vito; Guldi, Dirk Michael (Advanced Materials, 2011)
The impact of Förster resonant energy transfer (FRET) in CdTe quantum dot (QD) based photoelectrochemical cells is investigated. By deposition of different CdTe QD sizes onto indium on oxide electrodes, FRET across the photoactive film could be obtained, resulting in a 25% enhancement of the photon-to-current efficiency when compared to reference systems that lack FRET. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.